Concept of Nursing Care in Daily Life Activities - Hajiyeva Saodat Maksudovna; Avezova Nafisa Najmiddinovna (Лучшие интеллектуальные исследования, 2024)
Annotation: This lecture outlines the educational technologies and methodological recommendations for teaching the subject "Fundamentals of Nursing." These recommendations are designed taking into account didactic principles, methods, and tools for developing lecture and practical lesson technologies, and their essential characteristics for technologizing education. This lecture includes the curriculum, working curriculum, calendar-topic plan, educational technology developments, topic-specific slides, and developments of lecture and practical lesson topics of the "Fundamentals of Nursing" subject, intended for teaching the "Nursing" direction in medical colleges.